Eating disorders in medical students: prevalence, risk factors, comparison with the general population - Raluca Motorga; Mihaela Ionescu; Florina Nechita; Daniela Micu; Iulia Băluțoiu; Maria Mădălina Dinu; Dan Nechita (Frontiers in Psychology)
ObjectivesThe main objectives were to investigate the prevalence of ED and associated risk factors among medical students in Romania, as well as to determine which variables may predict ED and to explore the differences between medical students and the general population.MethodsThe Eating Disorders Inventory questionnaire (EDI-3) was applied. Also, the body mass index of the students was calculated, socio-demographic information regarding personal and family medical history was collected (mental and chronic diseases, self-reported sleep difficulties in the past 6 months, family history of obesity) and potentially risky events (history of ridicule, major negative events, social pressure to be thin from family, friends, media).Results37.1% students are at risk of eating disorders, 41% females and 23% males, according to the EDI-3. 14.42% were underweight, 65.05% normal weight, 16.99% overweight and 3.53% obese. Compared to the nationally representative sample in Romania, medical students had significantly higher scores for ED risk and for all other psychological factors.ConclusionMedical students have a high risk of developing ED, even higher than the general population. Several factors were associated with the ED risk, including female gender, experiencing sleeping difficulties, feelings of ridicule, family pressure and media pressure, prior ED history, high BMI, negative events and family history of mental illness. The regression analysis showed that family pressure is a strong predictor for ED risk.